Factors influencing software development in complex IT Projects using Agile approaches - A single telecoms case study - Griebenouw, Willem (Department of Information Systems, 2022)
Customer's needs and wants are forever changing and organistion need to be able to rapidly respond to the shifts in the market coupled with changing customer behaviour. Companies are continuously striving for different and innovative approaches to address these challenges. Several different approaches ranging are used by these organisation which range from incorporating new technologies, developing new products and services, and thoroughly understanding customer needs and requirements. These approaches require the organisation to adapt and adopt to new ways of working and moving away from traditional project management methods to agile methods. However, this transition gives rise to challenges such as the natural human resistance to change, needing to ensure that staff remain positive during these periods of uncertainty and change, ensuring that the organization does not backslide into its old ways of working (whilst under immense pressure to conform), effectively prioritizing projects and resources, as well as managing the cultural shift required to support these (organisational) changes. Coupled with these various challenges is a steep learning and adoption curve that must be overcome if the newly embedded technologies and processes are to be successfully assimilated into the organization. Thus it is crucially important that organisation not only understand the benefits associated with transitioning to agile methods, but also those barriers that need to be overcome to ensure a successful transition. Therefore this research is aimed at providing insight into the barriers and benefits associated with transitioning from Traditional Project Management (TPM) methods to agile approaches, specifically in the context of large complex IT projects. Throughout the study an inductive approach to data analysis was used to categorise the findings into broader themes after which two frameworks were used to interpret these findings. The Technology organisation environment framework (TOE) as well as the Socio-Technical Theory (STT/STS) framework were used to interpret the findings obtained. TOE assisted in analysing the relationships between the organisation, the external environment and the technological environment in which it operates. STT/TSS supported the TOE framework by guiding the analysis of the technical subsystem (agile tools) in conjunction with the social subsystem (employees) within the organisation. The study included a combination of of agile- and non-agile practioners within a telecommunications organisation, who all had previous experience of working on complex IT projects in a traditional and agile construct. The research provides insights into those themes that are associated with these barriers, for example poor and ineffective management style being displayed, teams still using a traditional TPM mindset when placed under duress, ineffective agile adoption within the teams, poor change management within the organisation, lack of support from business to enable delivery, and ineffective or unclear roles within teams and management, etc. and also highlighted several benefits to the transitioning which include empowered teams that are able to function autonomously, improved transparency and visibility within teams, improved speed of delivering and improved performance metrics in use within the organisation. During the course of the research several differing opinions were found which lead to contradiciting themes arising as each team witnessed the agile transition and implementation differently, which highlighted areas of future research. For example team autonomy was identified as a benefit to the transition allowing for self-direction but also sighted as a negative themes where teams empowerment is lacking; Traditional Project Management methods still providing improved speed of delivery when compared to agile methods. Other examples include some teams being disempowered with little or no decision-making authority, whilst others were able to self-direct and manage. Measurement metrics had been identified as both an advantage as well as a barrier to successfully transition to agile approaches as some felt the teams were measured effectively, whist others lamented a lack of appropriate metrics.